Transfer Kebijakan dan Implementasi Program Bantuan Tunai Bersyarat (Conditional Cash Transfer/CCT) di Indonesia - Budi Larasati; Lina Miftahul Jannah (Department of Public Administration, Muhammadiyah University of Makassar, 2022)
This study aims to illustrate the policy transfer process for the Conditional Cash Transfer (CCT) program in Indonesia. The research approach used in this article is qualitative, with literature review as the data collection method. In simple terms, CCT is a type of social assistance that offers cash to beneficiaries when certain conditions are met. Indonesia has implemented CCT program since 2007 through the Family Hope Program (PKH). The implementation of PKH itself cannot be separated from the efforts of the international development community, such as World Bank and the Asian Development Bank (ADB), in transferring CCT policies. This is done through the production and dissemination of various knowledge products, arrangement of international conferences, as well as the provision of financial and technical assistance. These efforts were supported by policy opportunities which arose at the domestic level, and the active participation of local actors. Therefore, policy transfer can be understood as a process which involves not only the international, but also domestic political actors, who interact and collectively facilitate the transfer and implementation of a public policy. The transfer process is influenced by several factors. In the case of Indonesia, the local political dynamics became a policy opportunity that facilitated the CCT policy transfer process.